Legitimacy versus illegitimacy — transparency, integrity of financial markets and corporate governance: whither corruption? - A. ‘Arafa, Mohamed (Revista do Direito, 2018)
Ethics management globally is a swiftly growing reality with various countries placing substantial emphasis on anti-corruption initiatives. International organizations, including the United Nations (“UN”), Transparency International (“TI”), and the Organization for Economic Cooperation and Development (“OECD”) have created a number of anti-corruption creativities, for instance, the UN, promulgated an International Code of Conduct for Public Officials in 1996 . Moreover, the United Nations International Centre for Crime Prevention has established an Anti-Corruption Tool kit to ‘help U.N. Member States and the public to understand the insidious nature of corruption, the potential damaging effect it can have on the welfare of entire nations and suggest measures used successfully by other countries in their efforts to uncover and deter corruption and build integrity . In the same vein, TI, the only global non-governmental organization dedicated to battling corruption, seeks via education and information to dishearten corrupt activities and fraudulent performances as well as foster integrity and liability to achieve better governance